2018
DOI: 10.1080/10402004.2018.1496304
|View full text |Cite
|
Sign up to set email alerts
|

A Master Curve for the Shear Degradation of Lubricating Greases with a Fibrous Structure

Abstract: In this article, the mechanical aging behavior of lubricating greases with a fibrous structure is studied by aging fresh samples at controlled shear rates and temperatures in an in-house-made Couette aging machine. The rheological properties of fresh and aged samples were evaluated in a plate-plate rheometer. In the absence of oxygen, no chemical reactions occurred. The results showed that shear degradation is accelerated by increasing the temperature. This thermal effect can be described by an Arrhenius law. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 19 publications
(15 reference statements)
3
40
1
Order By: Relevance
“…According to Zhou et al [21], the mechanical degradation of grease is caused by pressure and shear stresses. According to Reference [22], grease may soften during aging and leak out of the bearing systems.…”
Section: Degradation Systems Of Greasesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zhou et al [21], the mechanical degradation of grease is caused by pressure and shear stresses. According to Reference [22], grease may soften during aging and leak out of the bearing systems.…”
Section: Degradation Systems Of Greasesmentioning
confidence: 99%
“…Zhou et al [21] studied the mechanical aging behavior of fibrous structured greases, such as the lithium complex soap with poly-alpha-olefin (PAO) base oil and the polyurea-thickened grease with ester base oil. They reported that in the absence of oxygen no chemical reactions occurred.…”
Section: Degradation Systems Of Greasesmentioning
confidence: 99%
“…This shear degradation will contribute to the mobility of the grease (Cann and Lubrecht (38)). It was shown in (Zhou et al (28)) that PU/E is an aging sensitive grease (low shear stability). Albeit its relatively low bleeding rate, a good film recovery can be observed after the churning phase (Fig.…”
Section: Overall Film Thickness Profilementioning
confidence: 99%
“…Changes in base oil content (due to evaporation) and additive content (due to oxidation) can be established by infrared spectroscopy [8,41], but its use is limited in monitoring mechanical degradation. Rather, it can be used as a justification that mechanical degradation is dominant by finding that chemical reactions do not take place [13,36].…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…For these greases especially, a model that includes other forms of degradation-particularly oxidation-is essential. A promising start to incorporating thermal effects (without oxidation) into mechanical degradation models has been introduced by Zhou et al [36]. Additionally, Osara and Bryant [23] provide a DEG-based approach that incorporates thermal effects with high accuracy, and this proves a step forward in the development of a complete model.…”
Section: Future Directionsmentioning
confidence: 99%